2016
DOI: 10.1080/21505594.2016.1252016
|View full text |Cite
|
Sign up to set email alerts
|

Differing mechanisms of surviving phagosomal stress among group BStreptococcusstrains of varying genotypes

Abstract: Group B Streptococcus (GBS), a leading cause of neonatal sepsis and meningitis, asymptomatically colonizes up to 30% of women and can persistently colonize even after antibiotic treatment. Previous studies have shown that GBS resides inside macrophages, but the mechanism by which it survives remains unknown. Here, we examined the ability of 4 GBS strains to survive inside macrophages and then focused on 2 strains belonging to sequence type (ST)-17 and ST-12, to examine persistence in the presence of antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 55 publications
(57 reference statements)
11
70
0
Order By: Relevance
“…Moreover, inhibition of the acidification of the phagosome significantly reduced the ability of GBS to survive in macrophages, suggesting that acidic pH is needed for GBS to survive phagosomal stress. This reduced survival, however, was not observed in all of the strains examined, suggesting that diverse strains of GBS are using alternative mechanisms to withstand phagosomal stress (114).…”
Section: Gbs Survival Inside Phagocytesmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, inhibition of the acidification of the phagosome significantly reduced the ability of GBS to survive in macrophages, suggesting that acidic pH is needed for GBS to survive phagosomal stress. This reduced survival, however, was not observed in all of the strains examined, suggesting that diverse strains of GBS are using alternative mechanisms to withstand phagosomal stress (114).…”
Section: Gbs Survival Inside Phagocytesmentioning
confidence: 85%
“…Contradictory to these results, one study found no significant difference in survival inside murine macrophages between WT and ΔpilB strains (146). One possible explanation for this difference could be that different strains were used, which may vary in the mechanism used to survive inside the phagosome (114). The pilus backbone protein specific for ST-17 lineages, Spb1, was also shown to enhance both phagocytosis and intracellular survival of GBS.…”
Section: Gbs Survival Inside Phagocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The current study demonstrated that distinct GBS lineages differed in their ability to be phagocytized by and survive within macrophages. 12 Specifically the GBS ST-17 isolate persisted longer in macrophages compared with ST-19 and ST-12 strains, despite having similar impact on macrophage viability. Interestingly following internalization, 24 hours post infection the ST-17 strain exhibited higher transcript levels of key virulence factors (cylE, scpB, lmb, and fbsA) compared with the ST-12 strain.…”
mentioning
confidence: 90%
“…In this issue of Virulence, the authors of the article entitled "Differing mechanisms of surviving phagosomal stress among group B Streptococcus strains of varying genotypes" examined how lineage difference may impact GBS tolerance to antibiotics and various stress conditions, as well as intracellular persistence in phagocytic cells. 12 Phagocytic cells such as macrophages and neutrophils play an important role in innate immune defense against classic extracellular pathogens such as GBS. Pathogens that can persist within phagocytic cells and survive the phagolysosomal environment not only resistant phagocytic clearance, but may more readily disseminate into other bodily tissues.…”
mentioning
confidence: 99%